The Impact of Income Inequality and Income Level on CO2 Emissions in Central Asian Countries - Abdrakhmanova, Dinara; Dulambayeva, Raushan (International Journal of Energy Economics and Policy, 2025)
Income inequality has recently viewed not only as a factor affecting social stability, but also as a predictor of environmental sustainability and public health. This study examines the impact of income inequality and income levels on CO2 emissions in Central Asian countries. The aim of the article is to empirically test the environmental Kuznets curve (EKC) hypothesis and to analyze the relationship between income inequality and CO2 emission level. The analysis is based on panel data for Central Asia using regression and polynomial models. An additional analysis of socio-economic and environmental indicators provided deeper insight into the structural problems faced by the region. The study results confirmed the existence of an inverted U-shaped EKC, describing the relationship between income level and CO2 emissions. Regarding the impact of income inequality on environmental pollution, a country case study of Kazakhstan revealed no direct effect of income inequality on emissions. The impact of income inequality on CO2 emissions is indirect, occurring through other factors such as the industrial structure of the economy and urbanization. Therefore, in developing policies aimed at reducing emissions, it is necessary to apply an integrated approach, that takes into account the interconnection of social, economic, and environmental factors.